Memory Performance Attacks: Denial of Memory Service in Multi-Core Systems - Moscibroda, Thomas; Mutlu, Onur (USENIX SECURITY 2007: 16th USENIX Security Symposium, Boston, Massachusetts, USA, 2007)
We are entering the multi-core era in computer science. All major high-performance processor manufacturers have integrated at least two cores (processors) on the same chip — and it is predicted that chips with many more cores will become widespread in the near future. As cores on the same chip share the DRAM memory system, multiple programs executing on different cores can interfere with each others’ memory access requests, thereby adversely affecting one another’s performance. In this paper, we demonstrate that current multi-core processors are vulnerable to a new class of Denial of Service (DoS) attacks because the memory system is “unfairly” shared among multiple cores. An application can maliciously destroy the memory-related performance of another application running on the same chip. We call such an application a memory performance hog (MPH). With the widespread deployment of multi-core systems in commodity desktop and laptop computers, we expect MPHs to become a prevalent security issue that could affect almost all computer users. We show that an MPH can reduce the performance of another application by 2.9 times in an existing dual-core system, without being significantly slowed down itself; and this problem will become more severe as more cores are integrated on the same chip. Our analysis identifies the root causes of unfairness in the design of the memory system that make multi-core processors vulnerable to MPHs. As a solution to mitigate the performance impact of MPHs, we propose a new memory system architecture that provides fairness to different applications running on the same chip. Our evaluations show that this memory system architecture is able to effectively contain the negative performance impact of MPHs in not only dual-core but also 4-core and 8-core systems.